Sufism with the Integration of Humans: Seyyed Hossein Nasr’s Perspective - Riyaz, Aamir (Philosophy and Progress, 2024)
In this research paper, I aim to explore and discover the relation of Sufism with the integration of humans in the light of Seyyed Hossein Nasr’s view. I will also discuss the fundamental principle of Sufism, the historical development of Sufism, Seyyed Hossein Nasr’s view on Sufism, the spiritual trends in Sufism, Classical as well as the Modern approach to Sufism, and finally Sufi thoughts and Practices. Sufism, which, in my opinion, is a psycho-physical analysis, is a philosophy of love and God-intoxication. Initially, it was ascetic and devotional but later became speculative and doctrinal. It is a path of spiritualism and achievement of purity and gnosis of God. It is a philosophy that is as old as Islam and an essential part of it. The Sufi practice comprises the dogma of love towards God through the love of human beings, purification of the soul, the process of detachment, simplicity, and service to humankind. Most Sufis put an undivided importance on the moral value system and the sacred relation of Murshid (Guide) and Murid (Disciple). If we analyze these principles of Sufism, then it becomes clear that Sufism is a philosophy that promotes communal harmony, peace, tolerance, and co-existence in society. Seyyed Hossein Nasr explains Sufism as the marrow of the bones or the internal aspects of the Islamic revelation is the means par excellence whereby Tawhid is achieved. The integration of human beings implies the awareness of the One and the transformation of the countless in the light of the One. It is, therefore, the full realization of that faith or Iman, which is the fundamental basis of Islam. Philosophy and Progress, Vol#73-74; No#1-2; Jan-Dec 2023 P 113-129